Effects of Urbanization on Native Bird Species in Three Southwestern US Cities - Hensley, Christopher B.; Trisos, Christopher H.; Warren, Paige S.; MacFarland, Jennie; Blumenshine, Steve; Reece, Joshua; Katti, Madhusudan (Frontiers in Ecology and Evolution, 2019)
Urbanization presents novel challenges to native species by altering both the biotic and abiotic environment. Studies have attempted to make generalizations about how species with similar traits respond to urbanization, although existing results are idiosyncratic across cities and often fail to account for seasonality. Here, we present a comparative study in three US cities: Fresno, California; Tucson, Arizona; and Phoenix, Arizona. Using presence-absence data to define regional bird species pools and urban assemblages in non-breeding (winter) and breeding (spring) seasons, we tested whether urban avian assemblages were a random subset of regional assemblages on the basis of both traits and phylogeny, and whether urbanization was associated with homogenization among avian assemblages. We found evidence for non-random trait filtering into urban assemblages, including of diet guilds, migratory status, and primary habitat, but filtering differed across cities and seasons, being strongest for diet and in Fresno. There was no evidence for non-random phylogenetic-based filtering in urban avian assemblages. Dissimilarity in species and diet guild composition within each season was higher between cities than between regional species pools. These findings show the potential for biotic differentiation as opposed to homogenization as the outcome of environmental filtering processes operating on species traits across cities and seasons.